Contribución a una política económica urbana - La Padula, Ernesto (1959)
The author points out the necessity of a regulating plan for the city of Cordoba which considers the problems that have come forth as a result of the concentration of administrative and commercial activities, in addition to the settling of new industries and the increase of population, accentuating the lack of equilibrium between free spaces and builded spaces and the difficulties in public services and means of transport.